Pengaruh Pemberian Dosis Pupuk Urea terhadap Respon Pertumbuhan dan Produksi Tanaman Sawi Putih (Brassica Chinensis L.) dalam Polybag - Charly Mutiara; Yovita Yasintha Bolly (Fakultas Pertanian, Universitas Nusa Nipa, 2025)
Research on the effect of urea fertilizer dosage on the growth response and production of Chinese cabbage plants in polybags, has been conducted in Nangameting Village, East Alok District, Sikka Regency from August to November 2024. The purpose of this study was to determine the effect of urea fertilizer on the growth and production of Chinese cabbage plants. The design used in the study was a Randomized Block Design (RAK) with five (5) treatments and four (4) replications so that twenty (20) experimental units were obtained, namely M0 (control), M1 (1 gr / polybag), M2 (3 gr / polybag), M3 (5 gr / polybag), and M4 (7 gr / polybag). The results showed that urea fertilizer administration had no effect on plant height and number of leaves in the first observation (14 hst), and in the second observation (28 hst) it had a significant effect on both variables. Meanwhile, for the production variable (wet weight of mustard greens) it showed that the urea fertilizer dosage treatment had a significant effect at the 1% and 5% unit BNT levels.